RANCANG BANGUN TIMBANGAN DIGITAL TERINTEGRASI INFORMASI BMI DENGAN KELUARAN SUARA BERBASIS ARDUINO MEGA 2560 - Medilla Kusriyanto; Aditya Saputra (Teknoin, 2016)
Digitally height and weight of human body measuring instrument based sound module arduino is a modern measuring instrument that serves to measure the height and weight of the human body and provides information on BMI (body mass index) and weight of the human body. This tool is designed using ultrasonic sensors SRF-04 as a measurement of height and Load Cell as a measurement of weight and has an LCD display and output ofthe sound module. This tool has a maximum height limit measure measuring 200 cm and maximum weight limit of200 Kg. The working principle ofthis tool is arduino read wheter object is to use the tool if yes then the sensor will transmit data to the mierocontroller and the data will be displayed through the LCD and will be read out via the sound module. The information to be read is the weight, height, BMI, BMI status, ideal weight. From the results of testing this tool has a fault or error in the measurement of the weight of 0,43%. And measurement error or error in height measurement of 0, 72%.